Impact of Training and Demonstration on Integrated Crop Management in Transplanted Paddy in Chamarajanagar District of Karnataka, India - Sunil, M; Hanagi, Chandrakala; Yogesh, G.S (Journal of Extension Education, 2022)
Altogether, 11 practices were selected as criteria to evaluate the farmers on the extent of knowledge gained and adoption of rice production technologies as a result of training programmes conducted by Krishi Vigyan Kendra in Chamarajanagar district of Karnataka. The study revealed that the knowledge gained by farmers about the production technologies for rice ranged from 0% (mechanical harvesting) to 100% (hybrid variety and weed management). The adoption of hybrid rice variety KRH-4 was 100 % The results indicate that there are greater possibilities of increasing productivity and profitability of the rice crop with adoption of improved techniques in Chamarajanagar district of Karnataka, India.